Phytochemical study and evaluation of cytotoxic and genotoxicproperties of extracts from Clusia latipes leaves - Bailon Moscoso, N. (2015)
Some species of the Clusia genus have been shown to have important biomedical properties, includingthe ability to inhibit tumor growth in vitro and the usefulness for skin care. In this study, we exam-ined the cytotoxic effect of hexane, ethyl acetate and methanol extracts from Clusia latipes Planch. &Triana, Clusiaceae, leaves on survival of human prostate cancer cells (PC-3), colon cancer cells (RKO),astrocytoma cells (D-384), and breast cancer cells (MCF-7). The ethyl acetate extract displayed the mostsubstantial cytotoxic effect. However, using a Comet assay, we observed that the hexane extract induceda genotoxic effect (DNA damage) on human lymphocytes in an in vitro model. Chromatographic purifi-cation of the C. latipes hexane extract led to the isolation and identification of friedelin, friedolan-3-ol,and hesperidin as active cytotoxic compounds in hexane extract, while -amyrine was identified as anactive cytotoxic compound in the ethyl acetate extract of C. latipes, thereby supporting further stud-ies of the molecular mechanisms underlying the effect of these secondary metabolites on cancer cellsurvival.